Effects of Lignin-Based Hollow Nanoparticle Structure on the Loading and Release Behavior of Doxorubicin - Zhou, Yu (Materials (Basel), 2019)
Because of their exceptional absorption capacity, biodegradability, and nontoxicity, nanomaterials fabricated from renewable natural resources have recently become an increasingly important research area. However, the mechanism of drug encapsulation by lignin nanoparticles and the role of nanoparticle structure on the stability and loading performance still remain unknown. Herein, lignin hollow nanoparticles (LHNPs) were prepared and applied as promising vehicles for the antineoplastic antibiotic drug doxorubicin hydrochloride (DOX). The hydrogen bonding and π−π interactions contributed to the encapsulation of hydrophilic DOX by LHNPs with hydrophobic cavities. The encapsulation of DOX was enhanced by the pore volume and surface area. In addition, the nanoparticles contributed to the cellular uptake and the accumulation of the drug within HeLa cells. This work provides a scientific basis for future studies on the selective entrapment properties of hollow polymer nanoparticles derived from biomass material as vehicles for overcoming pharmacokinetic limitations.